The aspect of self-organization in the formation of an effective educational system in college - M. Dorozhkin, Evgeniy; Yu. Scherbina, Elena; N. Arefiev, Oleg (International Journal of Engineering and Technology, 2018)
The urgency of the problem under investigation is determined by the need to identify and develop the basic theoretical and methodological foundations of the process of self-organization aimed at developing the mechanism of self-development and achieving the desired result (goal) of college educational system in the current socio-economic situation. The purpose of the article is to scientifically substantiate the theoretical and methodological foundations of the process of self-organization of the educational system of college aimed at developing a mechanism for self-development and achieving the desired result in the preparation of highly qualified specialists for professional adaptation and career growth in the labor market. The leading method of research is the analysis and generalization of scientific provisions on this topic. The article substantiates scientific, methodological and technological tools, develops a conceptual model and algorithm for the process of self-organization of college educational system capable of forming a mechanism of self-development, of responding promptly to changes in the current social and economic situation and of achieving the desired result in the preparation of competitive specialists in demand on the labor market. The developed conceptual model, scientific-methodical and technological tools are aimed at solving practical problems of increasing the effectiveness of educational systems, identifying and forecasting the key factors of their self-development in the changing social and economic situation and in the external environment.Â Â